Dinamika Studi Kritik Sanad Hadis melalui Software Hadis Lidwa Pusaka - Hasibuan, Yusuf Firdaus; Rahmat (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2024)
This study aims to examine the evolution of the study of hadith sanad criticism with the Systematic Literature Review (SLR) approach, especially in the context of the use of Lidwa Pusaka Hadith software as a tool in sanad analysis. The main focus of this research is how paradigm shifts and methods in sanad criticism occur along with the development of digital technology, as well as the extent to which Lidwa Pusaka contributes to the effectiveness and accuracy of sanad studies. The methodology of this study uses the Systematic Literature Review approach with steps of identification, selection, data extraction, and synthesis from various relevant literature published in the period 2016–2020. Inclusion criteria include journal articles, proceedings, and thesis/thesis/dissertation that discusses sanad criticism, digital hadith studies, and the use of Lidwa Pusaka software in Islamic studies. The data collection technique is carried out by examining scientific documents through academic databases such as Google Scholar, DOAJ, and Garuda. Meanwhile, the data analysis technique is carried out through thematic analysis, by grouping data into main themes related to the development of sanad criticism methodology and the role of digital software, especially Lidwa Pusaka, in supporting hadith research. The results of the study show that there has been a significant evolution in the approach to sanad criticism, from a conventional approach to a software-based digital approach. Lidwa Pusaka specifically acts as an effective means of accessing matan and sanad hadith systematically and quickly, thus helping to speed up the process of verification and classification of hadith. The conclusion of this study emphasizes the importance of integrating technology in Islamic studies, as well as opening up new space for the development of a more efficient, accurate, and inclusive methodology of hadith criticism.